The Transformation Form of Begawai Dance in the Cooking Ceremony Phenomenon at Gawai Ceremony of Talang Mamak - Rian Indrasanjaya; Kasiyan (Mudra : jurnal seni budaya, 2025)
The Gawai Ceremony of the Talang Mamak tribe includes various communal practices that are considered mandatory by the community based on their traditional rules and beliefs. In the ceremony, the phenomenon of women’s cooking inspired a dance work entitled “Begawai.” Unfortunately, the creative process transformed cultural practices into dance, resulting in the loss of their original cultural identity. This study aims to describe 1) the Gawai ceremony of the Talang Mamak tribe, 2) the transformation of the phenomenon in the Gawai ceremony of the Talang Mamak tribe into the Begawai dance, and 3) the results of the creative process in the Begawai dance. This study uses a descriptive-qualitative methodology with a semiotic approach. The results showed that 1) the series of Gawai ceremonies consisted of Melekat Janji, Petang Mendaun, Menggantung Pauh-Pauh, Bunga Adat/dowry, Wedding Ceremony, Makan Beradat, Tiang Gelanggang, Mengadu Ayam, Acara Menyembang, and Ditegur Diajar. 2) In the Begawai dance, three transformation parts are identified: cockfighting, cooking, and traditional eating. 3) The creative process produced visuals: the cockfighting arena, cooking location, and the traditional dining atmosphere. The choreographer’s creative imagination inspired by cooking activities creates movements such as cutting, cleaning, scooping, stirring, and briding food. This research implies that the transformation experiences empirical gaps in cultural practices with a distinctive identity, so changing into a form of artistic activity in the creative process causes the loss of its cultural identity.